What role of the cGAS-STING pathway plays in chronic pain? - Wu, Jingxiang; Li, Xin; Zhang, Xiaoxuan; Wang, Wei; You, Xingji (Frontiers in Molecular Neuroscience, 2022)
Chronic pain interferes with daily functioning and is frequently accompanied by depression. Currently, traditional clinic treatments do not produce satisfactory analgesic effects and frequently result in various adverse effects. Pathogen recognition receptors (PRRs) serve as innate cellular sensors of danger signals, sense invading microorganisms, and initiate innate and adaptive immune responses. Among them, cGAS-STING alerts on the presence of both exogenous and endogenous DNA in the cytoplasm, and this pathway has been closely linked to multiple diseases, including auto-inflammation, virus infection, and cancers. Growing numbers of evidence suggest that cGAS-STING pathway involves in the chronic pain process, however, its role remains controversial. In this narrative review, we summarize the recent findings on the involvement of the cGAS-STING pathway in chronic pain, as well as several possible mechanisms underlying its activation. As a new area of research, this review is unique in considering the cGAS-STING pathway in sensory neurons and glial cells as part of a broader understanding of pain, including potential mechanisms of inflammation, immunity, apoptosis and autophagy. It will provide new insight into the treatment of pain in the future.